2015
DOI: 10.1021/acs.inorgchem.5b02054
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic and Biomolecular Hydrogen Evolution Catalysts

Abstract: There has been great interest in the development of stable, inexpensive, efficient catalysts capable of reducing aqueous protons to hydrogen (H2), an alternative to fossil fuels. While synthetic H2 evolution catalysts have been in development for decades, recently there has been great progress in engineering biomolecular catalysts and assemblies of synthetic catalysts and biomolecules. In this Forum Article, progress in engineering proteins to catalyze H2 evolution from water is discussed. The artificial enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 105 publications
(187 reference statements)
2
69
0
Order By: Relevance
“…On the other hand, cobalt-reconstituted heme-proteins, such as Mb and Cyt b562, have been shown to function in neutral water, but suffering from O 2 -intolerance and unsatisfactory TONs (up to 1,500) [311,312]. As an exception, cobalt-Cyt c552 from Hydrogenobacter thermophilus (Ht-CoM61A) displayed exceedingly high TON (270,000), albeit with a high overpotential value (730 mV) [313]. Being in the middle ground between biological and small-molecule catalysts, CoMC6*a appeared suitable for this challenge.…”
Section: Cobalt: Hydrogenase Activitymentioning
confidence: 99%
“…On the other hand, cobalt-reconstituted heme-proteins, such as Mb and Cyt b562, have been shown to function in neutral water, but suffering from O 2 -intolerance and unsatisfactory TONs (up to 1,500) [311,312]. As an exception, cobalt-Cyt c552 from Hydrogenobacter thermophilus (Ht-CoM61A) displayed exceedingly high TON (270,000), albeit with a high overpotential value (730 mV) [313]. Being in the middle ground between biological and small-molecule catalysts, CoMC6*a appeared suitable for this challenge.…”
Section: Cobalt: Hydrogenase Activitymentioning
confidence: 99%
“…18 These protein-based systems operate similarly to multi-molecular synthetic systems requiring diffusional interaction of catalyst and PSs (typically [Ru(bpy) 3 ] 2+ (bpy = 2,2′-bipyridine) and related derivatives) and achieve up to 520 turnovers (TON) of H 2 with sodium ascorbate as a sacrificial electron donor. 19 To enable direct supramolecular-like charge separation, an 18-amino acid peptide of cyt c 556 has been modified by covalent binding of both a diiron catalyst and a [Ru(bpy)(tpy)(H 2 O)] 2+ (tpy = 2,2′:6′2′′-terpyridine) PS. This system achieves 9 TON with a TOF of 11 h –1 and catalysis ceases with decomposition of the diiron catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Another direction being pursued is the application of protein‐engineering approaches to tuning metalloporphyrin molecular and electronic structure in engineered biomolecular catalysts. For example, cobalt porphyrin peptides and cytochromes have been developed as electrocatalysts for the reduction of protons to dihydrogen ,. Understanding and enhancing structure‐function relationships in these engineered biocatalysts may benefit from introducing changes in porphyrin conformation and interactions with the porphyrin to modulate activity.…”
Section: Discussionmentioning
confidence: 99%
“…Another direction being pursued is the application of protein-engineeringa pproaches to tuning metalloporphyrin molecular and electronic structure in engineered biomolecular catalysts.F or example,c obalt porphyrin peptides and cytochromes have been developeda se lectrocatalysts for the reduction of protons to dihydrogen. [140,141] Understanding and enhancing structure-function relationships in thesee ngineeredb iocatalysts may benefit from introducing changes in porphyrin conformationa nd interactions with the porphyrin to modulate activity.S tudies of model systems provide predictions of how ruffling will impact cobalt porphyrin electronic structure.I no ne study,W ang and Zhou found that enhancing Co(II) porphyrin ruffling increases the amounto fs pin density in the Co(II) d(z 2 )o rbital, [142] which has implicationsf or the interaction with substrate and reaction pathways.I na nother example, Grinstaff showed that highly distortedh alogenated iron porphyrins catalyze alkane oxidation. [143] As an examplei nabiological system,R ivera demonstrated that heme ruffling in enzyme-substratec omplexes of some heme-degrading enzymes activate the heme for degradation.…”
Section: Discussionmentioning
confidence: 99%